2005
DOI: 10.1093/humrep/deh743
|View full text |Cite
|
Sign up to set email alerts
|

Differential efficacy of group and individual/couple psychotherapy with infertile patients

Abstract: Results are suggestive of positive effects of psychotherapy for infertile patients. However, these results must be viewed with caution due to methodological and informational bias within the studies analysed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
1
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(79 citation statements)
references
References 33 publications
3
70
1
5
Order By: Relevance
“…This investigator states that interventions that emphasize education and skills training are more effective than those addressing emotional expression and support. Another study reviewing results from group interventions and individual/ couple psychotherapy (14) found that both intervention formats tend to decrease anxiety and depression. In another meta-analysis, Hammerli, Znoj, and Barth (15) analyzed 21 controlled studies about the efficacy of psychological interventions in terms of mental health indicators and pregnancy rates.…”
mentioning
confidence: 99%
“…This investigator states that interventions that emphasize education and skills training are more effective than those addressing emotional expression and support. Another study reviewing results from group interventions and individual/ couple psychotherapy (14) found that both intervention formats tend to decrease anxiety and depression. In another meta-analysis, Hammerli, Znoj, and Barth (15) analyzed 21 controlled studies about the efficacy of psychological interventions in terms of mental health indicators and pregnancy rates.…”
mentioning
confidence: 99%
“…The diagnosis of infertility, the medicalisation of conception including undertaking multiple medical procedures and awaiting unguaranteed pregnancy outcomes are all potent and social stressors. Heightened anxiety may negatively impact on the patient's fertility treatment journey [5,6] although the clinical benefits of psychosocial interventions in reducing emotional distress and in improving fertility treatment outcomes is still controversial [7,8,25]. Our study showed that self-selected music used for a short duration (15 minutes) before and after embryo transfer did not reduce anxiety but that women undergoing IVF expressed high levels of pre embryo transfer anxiety that is ameliorated following completion of the treatment procedure.…”
Section: Discussionmentioning
confidence: 67%
“…Lower levels of anxiety [5,6] and interventions directed to reduce these effects have been suggested to improve treatment outcomes [7,8] but there is little evidence for this providing clinical benefit. Music may be a simple therapeutic adjunct to IVF treatment, it has been shown to decrease anxiety and improve quality of life in other medical settings, and is easy to apply and of low cost [9].…”
Section: Introductionmentioning
confidence: 99%
“…In an analysis of 25 studies, Boivin et al showed decreased infertility-related distress with a psychosocial intervention 18 . In a later meta-analysis of 22 studies 19 , reduced infertility-related anxiety and depression were shown. Only one recent meta-analysis, by Hammerli et al 20 , who looked at 21 controlled studies (and excluded 363 others), noted no significant improvement in depression, anxiety, or mental distress with psychological intervention.…”
Section: 13mentioning
confidence: 97%